Anti-PRRSV effect and mechanism of tetrahydroaltersolanol C in vitro. Issue 3 (3rd March 2016) - Zhang, Song-Lin; Wu, Yi-Chun; Cheng, Fan; Guo, Zhi-Yong; Chen, Jian-Feng
Abstract : Porcine reproductive and respiratory syndrome virus (PRRSV) is an important arterivirus that causes substantial economic losses to the swine industry. Current control strategies against PRRSV are still inadequate and there is an urgent need for new antiviral therapies. Tetrahydroaltersolanol C (TD-C) is a new anthraquinone derivative isolated from the marine-derived fungi. In the present study, we first demonstrated its anti-PRRSV activity in vitro through assessing the inhibition of TD-C on cytopathic effect, viral ORF7 gene and N protein expressions, progeny virions production by 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide assay, relative-quantitative RT-PCR, Western blotting, and indirect immunofluorescence assay. Our experimental results showed that TD-C could significantly inhibit PRRSV replication in a dose-dependent manner. The 50% effective concentration, 50% cytotoxic concentration and the selectivity index were 12.11, 395.31 μM, and 32.64, respectively. Furthermore, the possible anti-PRRSV mechanism was explored by virucidal assay, virus adsorption inhibition assay, and the time-of-addition assay. The results showed that TD-C might inhibit the internalization and replication of PRRSV, but did not directly inactivate the virus or block its adsorption to cell surface. In conclusion, our findings indicated that TD-C possessed a significant anti-PRRSV activity, and provided a strong basis for further exploration of this compound as an antiviral agent against PRRSV.